Dominant Factor were Caused Eight Grade Students Errors in Solving on Cartesian Coordinate Multistep Routine and Non-Routine Modification Story Problems - Hendrayanto, Dhani Nur; Riyadi, Riyadi; Indriati, Diari (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
Giving a high level modification story problems with multistep routine and non-routine problems in cartesian coordinate learning is an effort to achieve optimal learning and also important because it has good effect for students. Less than optimal learning of cartesian coordinates for eight grade it was usually represented by the frequent of student errors occurrence on an ongoing basis in solving on mathematical problems in assignments and daily tests. This research purpose was to reveal the dominant factor were caused eighth grade student errors in solving on cartesian coordinate multistep routine and non-routine modification story problems. This research is a descriptive qualitative in type. Research data collection based on survey, interview, test and documentation.  The research subjects in this research were eight grade students of SMPN 4 Wonosobo. In this research 18 students of  eight grade students SMPN 4 Wonosobo as the research sample. The sampling technique it was used in this research is purposive sampling. The results of this research indicate the dominant factor were caused eighth grade student errors in solving on cartesian coordinate multistep routine and non-routine modification story problems is students difficulties.  Students difficulties such as compiling steps to solve problems in the form of multistep story problems, understanding the position conception of starting point with a certain point, understanding the conception of a perpendicular lines and a parallel lines to the X and Y axis, determining the distance of a point to certain point. The implication of this research is can obtain information about the dominant factor were caused student errors in solving on cartesian coordinate multistep routine and non-routine modification story problems as the relation to the current idealization of mathematics learning optimization and can be able for planing another appropriate and solution steps for the implementation of mathematics learning in an effort to minimize student errors.